Correlation of thyroid-stimulating hormone level with obesity in patients of polycystic ovary syndrome - Saha, Amrita; Shukla, Shashi; Preeti; Divya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Polycystic ovarian syndrome (PCOS), a heterogeneous endocrine disorder is most common in women of the reproductive age group. Thyroid disorders and PCOS are two of the most common endocrine disorders in women. Although the etiopathogenesis of hypothyroidism and PCOS is completely different, these two disorders have many common features. An increase in ovarian volume and cystic changes in ovaries have been reported in primary hypothyroidism. The aim of this study was to find the correlation of thyroid-stimulating hormone (TSH) level in obese and non-obese women, who were diagnosed to have PCOS. Methods: The data of 161 women who visited the institution for diagnosis and management of PCOS were included in the study. Demographic data like age, height and weight of the women at the time of diagnosis of PCOS were collected and subjected to analysis. Results: The results showed that 15% obese PCOS women had high TSH level and 7% non- obese PCOS had high TSH level. Conclusions: The result of the study suggests that higher level of TSH seen in obese PCOS women than non -obese PCOS women.